Micro-regularidade Gevrey de soluções de sistemas involutivos de edp's não lineares de primeira ordem - Barostichi, Rafael Fernando (2010)
Let u be a C2 solution for a Gevrey involutive system of _rst order nonlinear partial di_erential equations. In this work, we show that the Gevrey wave front set of order s of u is contained in the characteristic set of the involutive structure generated by the linearized operators associated to the given system. Our approach includes the study of Gevrey approximate solutions, a concept which we believe is of independent interest and could be applied to much more general situations.